Cloning and First Functional Characterization of a Plant Cyclic Nucleotide-Gated Cation Channel - Leng, Qiang (American Society of Plant Physiologists, 1999)
Cyclic nucleotide-gated (cng) non-selective cation channels have been cloned from a number of animal systems. These channels are characterized by direct gating upon cAMP or cGMP binding to the intracellular portion of the channel protein, which leads to an increase in channel conductance. Animal cng channels are involved in signal transduction systems; they translate stimulus-induced changes in cytosolic cyclic nucleotide into altered cell membrane potential and/or cation flux as part of a signal cascade pathway. Putative plant homologs of animal cng channels have been identified. However, functional characterization (i.e. demonstration of cyclic-nucleotide-dependent ion currents) of a plant cng channel has not yet been accomplished. We report the cloning and first functional characterization of a plant member of this family of ion channels. The Arabidopsis cDNA AtCNGC2 encodes a polypeptide with deduced homology to the α-subunit of animal channels, and facilitates cyclic nucleotide-dependent cation currents upon expression in a number of heterologous systems. AtCNGC2 expression in a yeast mutant lacking a low-affinity K(+) uptake system complements growth inhibition only when lipophilic cyclic nucleotides are present in the culture medium. Voltage clamp analysis indicates that Xenopus laevis oocytes injected with AtCNGC2 cRNA demonstrate cyclic-nucleotide-dependent, inward-rectifying K(+) currents. Human embryonic kidney cells (HEK293) transfected with AtCNGC2 cDNA demonstrate increased permeability to Ca(2+) only in the presence of lipophilic cyclic nucleotides. The evidence presented here supports the functional classification of AtCNGC2 as a cyclic-nucleotide-gated cation channel, and presents the first direct evidence (to our knowledge) identifying a plant member of this ion channel family.